Mechanism of Late Campanian–Early Maastrichtian oil shale deposition and its sequence stratigraphy implications inferred from the palynological and geochemical analysis - Walid Ahmed Makled; Tarek Foad Mostafa; Abu Bakr Fathy Maky (Egyptian Journal of Petroleum)
Understanding the organic rich sediment deposition mechanism is vital for the purposes of their exploration. This should reconsider the sequence stratigraphic framework and its associated paleoenvironmental setting. The palynological and geochemical aspects of the organic rich beds from the Duwi Formation conducted on six phosphate mines in the Eastern Desert of Egypt are reported in the present study and they were used to investigate the paleoenvironmental settings that existed during its deposition. The palynomorph assemblages were dominated by moderately diverse and abundant dinoflagellates and in El-Nakheil, Wasif, Umm Hueitat and Mohamed Rabah mines and generally scarce palynomorph assemblages were generally detected at El-Beida and Younis mines. The dinoflagellates are mainly peridinioids, namely; Alterbidinium acutulum, Cerodinium obliquipes, Palaeocystodinium australinum and Phelodinium tricuspis, in addition to some gonyaulacoid such as Kleithriasphaeridium readei, Hystrichosphaeridium sp. A, Hystrichosphaeridium sp. B and Spiniferites supparus. These dinoflagellate assemblages are indicating Late Campanian–Early Maastrichtian age. The palynofacies analysis revealed enrichments with amorphous organic matter (AOM) at El-Nakheil and El-Beida mines, while the phytoclasts enrichments were found to be at the Younis mine. The enriched AOM samples are of Type I and II oil prone kerogen while the enriched phytoclasts are of Type III gas prone kerogen. In line with, the resulted kerogen types agreed with rock eval pyrolysis analysis. The integration of rock eval pyrolysis and other geochemical parameters with the palynofacies analysis indicated that the deposition of low organic matter sediments (TOC ∼ 0.04–1.77 wt%) took place in a low stand system-tract. On the other hand, the sediments of high organic matter content (TOC ∼ 9.66–22.23 wt%) were deposited in a transgressive system tract under low sedimentation rate. Eventually, the intermediate organic matter content sediments (TOC ∼ 8.39–22 wt%) were deposited in a high stand system tract during an active paleoproductivity and upwelling.